Implementing AWS : Design, Build, and Manage your Infrastructure : Leverage AWS features to build highly secure, fault-tolerant, and scalable cloud environments /: Design, Build, and Manage your Infrastructure : Leverage AWS features to build highly secure, fault-tolerant, and scalable cloud environments. (2019) - Wadia, Yohan; Udell, Rowan; Chan, Lucas; Gupta, Udita
No abstract available